(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2022)
The article revisits the concept of entropy in art as discussed by Gestalt psychologist and art theorist Rudolf Arnheim. His discussion of artworks and their reception as complex dynamic fields where the forces of entropy and orderliness counter and complete each other, are brought into dialogue with newer approaches, from the perspective of complexity theory and neuroscience, to the dynamics of perception and to entropic processes in the brain. I will argue that even though Arnheim’s observations can still be valuable for contemporary art criticism they need to be updated as they tend to overstate the tendency for order as well as the visual aspects of reception in the expense of multimodal and embodied aspects. In light of these observations, I will discuss contemporary cases of ‘entropic’ art through the moving image works of Marco Brambilla, their aesthetics as well as the ‘structural themes’ arising and the Gestalt processes involved in their reception.